(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the company’s rules or set of ideals is the code of ethics. This is the largest set of rules for all organization members. Being honest and professional in the workplace is part of the Code of Ethics and can lead to violations in your organization. Professional decisions and actions in an organization are part of the Code of Ethics. Organizational values should now approach the problem. Help staff, employees, or others better understand the company or organization’s code of ethics. This study worked on the scope of evaluation of the HR practices of Montalban Waterpark Resort in relation to the business code of ethics basis for standardization. After reviewing existing theories, researchers developed a conceptual framework for why business ethics standards are important to businesses. A questionnaire is then used to determine if there is a significant difference in the ratings of two groups of respondents, male and female. To assess employee satisfaction, employees were presented with the results of four variables (Hiring, Professional Practices, Safety Standards, and Conflict of Interest). In addition, the two groups of respondents’ problems and managers’ solution approaches were discussed. This research may serve as a reference for employees as the code stimulates debate about ethics and compliance and empowers them to address the ethical dilemmas they encounter in their daily work. It also serves as a valuable reference tool to help employees find relevant ethics-related documents, services, and other resources within their organization.